PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA PELAKU UMKM MIE AYAM DAN CENDOL DAWET - Eva Dora; Tutut Dewi Astuti (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2023)
Micro, small and medium enterprises (MSMEs) have an important role as stabilizers and dynamizers in economic growth in a country, especially developing countries such as Indonesia. However, the problem that is often faced by MSMEs is the lack of knowledge about financial reports, this causes financial performance to not be clearly known. The purpose of this training is to provide understanding and knowledge in making financial reports correctly and designing reports simply for MSME actors. The method used in this training starts with the pre-survey preparation stage, program implementation, discussion, and evaluation. This training has been achieved and is evidenced by the success indicators as measured by assessing the understanding and knowledge of the participants through several questions that have been given, the value obtained is 20% before the training. then after the training the number increases to 80%. Based on the data obtained, with this training activity it can be said that the understanding and knowledge of the participants has increased significantly.